PENGARUH FLUKTUASI HARGA MINYAK DUNIA, BELANJA MODAL, DAN PERTUMBUHAN EKONOMI TERHADAP KETIMPANGAN PENDAPATAN DI INDONESIA - Wita Musfetriyeti (Universitas Negeri Padang, 2017)
This study aims to analyze the effect of world oil price (X1), capital expenditure (X2), economic growth (X3), to income inequality (Y) in Indonesia. This type of research is descriptive and associative. The data used is secondary data the time period 1985-2015. with data collection techniques documentation and literature study. Data analysis used is descriptive analysis and inductive analysis. In the inductive analysis there are several tests: (1) Multiple Linear Regression Test; (2) Analysis of Classical Assumptions; (3) Test t and Test F. Research results show that world oil prices have a significant and positive impact on inequality in Indonesia, capital expenditure have a significant and negative impact on inequality in Indonesia, and economic growth has no significant and negative impact on income inequality in Indonesia α = 0.05.